Geographies of (dis)protection: Sketches in anti-racist mental health - Jeannette del Carmen Tineo Durán (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2024)
This essay explores the affective maps or emotional archives of racialized communities in Spain, specifically focusing on the Caribbean Afro-diaspora in Madrid. It questions how migratory grief is prescribed by the government without taking into account the colonial wound, racial trauma, and the geopolitics of emotions, while delving into everyday structural racism. Drawing from decolonial theory and Black feminism, as well as narrative healing practices created by migrant collectives, qualitative research was conducted during the period 2023-2024, involving 25 in-depth interviews and two group workshops with the participation of 15 anti-racist activists. After an introduction framed by an autobiographical narrative within the anti-racist conversation, key aspects of the notion of migratory grief are highlighted, associating it with the colonial wound. Subsequently, some characteristics of memory as geographies of abandonment are emphasized. Finally, I turn to the notion of imagination, in the form of collective daydreams or fantasies that activate the hope of transcending the borders of European racism. The article builds bridges between community health, an intercultural perspective, and anti-racism.